Marketing Management's View of Integrated Marketing Communications - Erdi Adrimurlan Chaniago; Nafiah Ariyani (International Journal Labs, 2023)
Regardless of the value of the products sold, marketing activities are an integral part of running a business. Without proper marketing, the business will not be able to achieve optimal sales. Today's businesses must incorporate marketing and business activities into their overall strategy for success. This is due to the fact that modern business attaches great importance to integrated marketing communications. Some businesses use a combination of ineffective and inefficient marketing communications that do not communicate their message properly to potential buyers or consumers. This results in a constant need for remarketing efforts by businesses to reach their intended audience. This study used a case study approach to collect data. It uses interviews with medium and small business owners to gather information regarding the importance of integrated marketing communications. In addition, he took inspiration from other research to gather information on the advertising strategies and approaches of Whole Milk SMEs. Upon completion, this study demonstrates the important role of integrated marketing communications in Whole Milk SMEs. It also reveals what marketing strategies Pure Milk SMEs are using and how they plan to further promote their brands.